Remarks at the High Level Meeting on Famine Response and Prevention - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group (WBG), spoke about how famine can affect children, their health, and their ability to learn and to earn a living, which can hinder development progress for a generation. He reported on the Famine Response Package. He noted important lessons learned through these interventions. First, expanding new partnerships is important to deliver in challenging environments. Second, flexibility is key to adapting to emerging needs. Third, with protracted and recurrent crises as the new normal, more has to be done to ensure that the information, systems, and processes to help countries cope are in place, and to find new solutions through innovative partnerships including the private sector.